WORD STRESS IN ENGLISH AND UZBEK - Khalilova Bakhora; Yakubov Fakhriddin (TADQIQOTLAR, 2025)
Annotation:This article examines the concept of word stress in the English language and its importance in correct pronunciation and effective communication. Word stress plays a crucial role in distinguishing meaning, improving intelligibility, and developing listening and speaking skills. The article discusses the definition of word stress, its main types, and common stress patterns in English words. Special attention is given to the difficulties faced by Uzbek learners of English and the typical mistakes they make in stress placement. The study highlights the significance of teaching word stress systematically and suggests practical approaches for improving learners’ pronunciation competence.